(3GdCSHGH hGdYdGeGJs - (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI hGdMeO dg bGd GdGeGe aj gPg GdeLdOI eG cGfJ MGLJj Edjg GVWQGQjI YfO eTGggI GdeQVj heYGdLJge djchf OGFekG Hjf s
(3BNQgG (B:s
(3hQHeG daj ajg GSJYeGd GdedM hGdNd Ydi ehVY GdYVI hGcf CYde Je cJGH GdGSHGH hGdYdGeGJ s
(3Gdajde eXdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs